Hospital antimicrobial stewardship funding and resourcing impact on broad-spectrum antibiotic use: a cross-sectional study - Megan Tu; Zong Heng Shi; Valerie Leung; Kevin A Brown; Kevin L Schwartz; Nick Daneman; Bradley J Langford (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract